Evaluasi Peralatan Dalmas dan PHH Polri dalam Rangka Persiapan Pengamanan Pemilu 2024: Evaluasi Peralatan Dalmas dan PHH Polri dalam Rangka Persiapan Pengamanan Pemilu 2024 - Harvin Raslin (Pusat Penelitian dan Pengembangan Polri, 2023)
In carrying out the main task of maintaining domestic security and public order, the Police are required to anticipate disturbances in Kamtibmas (public security and order). The preferred service pattern is the pre-emptive and preventive strategy to anticipate anarchic rallies and prevent them from spreading. In facing the 2024 Election, the readiness of equipment of the Dalmas unit of the Samapta and PHH unit of the Brimob, both individually and collectively, needs to be evaluated, to what extent the equipment of the Dalmas and PHH in the area is adequate both in quantity and quality. This research uses a mixed method which is a combination of quantitative and qualitative methods with a total of 2,635 respondents. From the results of research and analysis, it can be concluded that the real condition of the Dalmas and PHH equipment in terms of quantity is still quite adequate. However, there are some equipment that needs to be added, especially for units that often face crowds. The equipment that needs to be added are shields, helmets, batons, smooth bore weapons, and tear gas. In terms of material quality, some of the equipment deployed in the field were found to be cracked, broken, loose, and soaked, such as smooth bore weapons, helmet glass, and shields. In addition, an improvement in the quality of equipment used for the preparation of securing the 2024 Election or other situations is necessary. This improvement is needed for the comfort and protection of personnel themselves when facing or colliding with the public. Therefore, it is concluded that there is a need to add equipment and improve the quality of materials in the Dalmas and PHH equipment to improve the quality of the equipment in maintaining domestic security and public order.